The Influence of Halal Labels, Brand Image, and Product Quality on Purchasing Decisions of Skintifict Products with Word of Mouth as a Moderating Variable (Study on Muslim Adolescents in Palu City) - Devi Novianty; Amiruddin Kadir; Sudirman (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of halal labels, brand image, and product quality on purchasing decisions for Skintific cosmetic products, as well as to evaluate the role of word of mouth in moderating the relationship between research variables among Muslim adolescents in Palu City. This study is motivated by the increasing demand for halal cosmetics by Muslim consumers and the phenomenon of digital marketing that shapes purchasing decision-making patterns through social influence and opinions on social media. The study used a quantitative method with the Structural Equation Modeling – Partial Least Square (SEM–PLS) analysis technique, and involved 200 respondents selected through purposive sampling. The results showed that halal labels, brand image, and product quality had a positive and significant effect on purchasing decisions. Word of mouth was proven to moderate all relationships, but with different dynamics: negative moderation of the relationship between halal labels and purchasing decisions, and positive moderation of brand image and product quality. This study provides academic and practical contributions in cosmetic marketing strategies for the Muslim adolescent consumer segment.